Withapubesides A–D: natural inducible nitric oxide synthase (iNOS) inhibitors from Physalis pubescens. Issue 47 (22nd November 2017) - Xia, Gui-Yang; Yao, Tie; Zhang, Bing-Yang; Li, Yang; Kang, Ning; Cao, Shi-Jie; Ding, Li-Qin; Chen, Li-Xia; Qiu, Feng
Abstract : Withapubesides A–D (1–4 ), candidates for the development of iNOS inhibitors, were isolated from Physalis pubescens . Abstract : Four new steroid glycosides, withapubesides A–D (1–4 ), were isolated from the stems of Physalis pubescens L. Their structures were elucidated primarily by NMR experiments. The absolute configurations of1 and2 were deduced by single-crystal X-ray diffraction and ECD data analysis, respectively. Compound3 has shown significant inhibitory activity against LPS-induced nitric oxide production in RAW 264.7 macrophages with an IC50 value of 12.8 μM and moderate cytostatic activity against human carcinoma cells (786-O, C4-2B, 22Rvl, A375 and A375S2) with IC50 values in the range of 3.05–9.47 μM. Molecular docking simulation demonstrated that3 is bound in the inducible nitric oxide synthase (iNOS) active site heme pocket very well, which suggests that3 might be a candidate for the development of iNOS inhibitors.